New Candidates for PDT: Lutetium, Indium and Zinc Phthalocyanines Substituted with PEGME-2000 Blocks - YİĞİT, CANAN USLAN (My University, 2019)
Phthalocyanines (Pcs) are macromolecules that have been the subject of research in many fields of application due to their unique structural properties. Unlike other tetrapyrrole derivatives, the conjugation of phthalocyanines is remarkable because of the benzene units in their chemical structures [1]. Aggregation and insolubility phenomena are the most important restrictions of the use of Pcs in many applications. The water solubility of Pc molecules plays a decisive role in biomedical research [2]. In this study, we have synthesized Zinc(II) (5), indium(III) (6), and lutetium(III) (7) phthalocyanines peripherally substituted with poly (ethylene glycol) (PEG) monomethyl ether 2000 (PEGME-2000) blocks via Sonogashira coupling reaction with high yields. We determined their photophysical, photochemical and photobiological properties. The photophysical and photochemical properties were determined in both DMSO and aqueous solutions. We elucidated the interactions of these compounds with DNA, BSA and determined the binding constants. Thermodynamic parameters, as well as thermal denaturation profile of double-stranded DNA were also examined to determine the type of binding mode of Pcs. According to our experimental data, we report that PEGME-2000 favors the formation of a binary complex between DNA, and phthalocyanine complexes. Therein, thermodynamic data suggest that this binding mode is indeed spontaneous under-reported conditions, and rather non-specific. Our results suggest that these compounds are efficient photosensitizers for photodynamic therapy (PDT) and that the binding ability of new phthalocyanines 5, 6, and 7 with BSA paves the way for their utilization as drug vehicle in blood plasma. References: [1] Pinto SMA, Tome VA, Calvete MJF, Pereira MM, Burrows HD, Cardoso AMS, Pallier A, Castro MMCA, Toth E, Geraldes CFGC (2016) 'Hie quest for biocompatible phthalocyanines for molecular imaging: Photophysics, relaxometry and cytotoxicity studies. J Inorg Biochem 154:50-59. [2] Durmuş M, Ahsen V, Nyokong T (2007) Photophysical and photochemical studies of long chain- substituted zinc phthalocyanines. J Photochem Photobiol A Chem 186:323-329.